TRADITIONAL, VERNACULAR AND NEWLY DEVELOPED CONSTRUCTION TECHNOLOGIES APPLIED TO THE SLAVE DESCENDENT WOMEN CLAM GATHERS COMMUNITY OF POVOAÇÃO DE SÃO LOURENÇO IN PERNAMBUCO, BRAZIL - Santos-Filho, Plínio; Andrade Reis, Carla; Gomes dos Santos Filho, Antônio; de Medeiros, Leandro Leonel; Leônidas Gomes, Euma; Oliveira de Queiroz, Malthus; Andrade, Ana Maria; Cavalcanti, Virginia; Carneiro da Cunha Filho, Francisco (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
The costal tropical areas of Northeast of Brazil, where manual labor is of utmost importance due to the irregular landscape in the sugar cane plantations, still maintains a vast tradition of vernacular housing in the wattle and daub (taipa) construction technique. This paper, addresses this historical building methodology in the village of Povoação de São Lourenço in the county of Goiana, State of Pernambuco, as the introduction of a new Technological Vocational Center, CVT, in part funded by the Brazilian Ministry of Science and Technology, starts to impact the local housing and building tradition. Yet, it appears that much of the local earth construction knowledge could and should be preserved. In existence for at least 4 centuries, this slave descendent population of 2,500 has the church of São Lourenço, the second oldest church of Brazil. Bordering the Goiana River, the geographical boarder between the States of Pernambuco and Paraíba, the local population impacts greatly the environment by the cutting of the remaining of the tropical forest and mangrove trees and bushes for cooking and wood for building. The introduction of alternative energy technologies (solar and high efficiency wood stoves), adobe and lime/cement stabilized earth blocks, along with vault and dome construction options can efficiently reduce the local forest and mangrove wood consumption, in an area that has been identified to be a forest sanctuary to preserve.